Improving Social Skills through Project Based Blended Learning Model at SMAN 3 Ambon - Riwan Ninilouw; Lisye Salamor; Ridwan Hatala (IJRAEL: International Journal of Religion Education and Law, 2022)
Social skills are skills acquired through the learning process used in dealing with their environment in a good and appropriate way. Social skills are types of skills that include skills, mutual cooperation, please help and carry out activities as social beings to meet the needs of the community. Researchers have conducted a survey of the general condition of the research site. The research location in question is SMAN 3 Ambon. The results of the study show that students are more likely to increase their competence individually than to develop collectively or in groups. The purpose of this study was to determine the improvement of social skills through a project based blended learning model at SMAN 3 Ambon. This research is located in SMAN 3 Ambon which is located on Jln. Beach, Three Houses Village. Retrieval of information in this study through observation, tests and documentation. This research uses the CAR method, CAR is a research conducted by the teacher in the classroom itself through self-reflection with the aim of improving performance as a teacher, so that student learning outcomes increase. The results of this study, to improve social skills, teachers must develop learning models that can develop students' active character and can form cooperation with each other at school and in the community.